A constituição de sentidos nas provas de redação do ENEM: uma análise enunciativa de designações - Sá, Ana Cecylia de Assis e (2022)
Since its inception, the National High School Exam has been the object of study of many researches in the field of linguistics, either from the discursive test - the essay - or the objective test, in the area of "Languages, codes and their technologies". However, the most studied areas of linguistics are morphology, syntax and semantics, but without the enunciative bias. Thus, this thesis has the general objective of analyzing how the enunciative process happens in ENEM's writing tests, through the concept of the Semantics of the Event. As specific objectives, we propose to: a) analyze the process of meaning of the topic-enunciations and motivating texts; b) show how this meaning is built; c) seek a contribution to language teaching by building an activity model for the analysis of topic-enunciations and motivating texts in writing classes. To this end, in accordance with the applied nature of qualitative research ( descriptive and propositional), the object of analysis of this study consists of 20 ENEM essay tests, from 1998 to 2018, when the exam completes 20 years of existence. The corpus, in turn, is the keywords (open, command, and theme) identified in the text and in the motivating texts related to it, which will be analyzed using a methodology specific to Event Semantics, the DSD (Semantic Domain of Determination). The choice for this corpus and for this object was due to the importance attributed to this exam and to the relevance of the writing test in the high school context, which increasingly focuses on the exploration of meanings in the proposals of argumentative essay production and on the correct interpretation of the topic-enunciations. To act in the analysis of our data, massively will be used the studies of Guimarães (1987; 2004; [2002]2017; 2018), since it is the elaborator of the theory from which we will move all our discussion and analysis. As a result of our research, based on the analyzes carried out, we ensure that the enunciative game that takes place between the theme-statements and the statements that make up the motivating texts is capable of favoring the interpretation of the proposal. Finally, we emphasize that the enunciative study of the ENEM writing tests favors the interpretation of the proposals and the theme statements, in favor of the search for the maximum score in this exam.